2018
DOI: 10.1007/s00482-018-0294-6
|View full text |Cite
|
Sign up to set email alerts
|

Die deutsche Version der Bath Body Perception Disturbance Scale (BBPDS-D)

Abstract: This German translation and cross-cultural adaptation of the original English version of the BBPDS is a valid instrument to assess body perception disturbances in German speaking CRPS patients. Future research should further assess the impact of body perception disturbance on treatment outcome and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…This subtle difference in phrasing might be the reason why the internal consistency of the German version (including the item on attention) is much higher (Cronbach's alpha = 0.92) than seen in previous studies. 57 We propose a revised B-CRPS-BPDS (r-B-CRPS-BPDS) excluding the item on attention (see supplementary material for a downloadable version with scoring instructions). Alternative approaches would be to investigate whether rewording this item in the English B-CRPS-BPDS improves its validity, or to create two separate items that independently capture hypervigilance towards, and inattention for the CRPS-affected limb(s).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This subtle difference in phrasing might be the reason why the internal consistency of the German version (including the item on attention) is much higher (Cronbach's alpha = 0.92) than seen in previous studies. 57 We propose a revised B-CRPS-BPDS (r-B-CRPS-BPDS) excluding the item on attention (see supplementary material for a downloadable version with scoring instructions). Alternative approaches would be to investigate whether rewording this item in the English B-CRPS-BPDS improves its validity, or to create two separate items that independently capture hypervigilance towards, and inattention for the CRPS-affected limb(s).…”
Section: Discussionmentioning
confidence: 99%
“…51 A prospective study found that body perception disturbance decreased in the first 12 months following the onset of CRPS, along with a decrease of pain, CRPS severity, and disability. 1 However, crosssectional studies found either no effect of disease duration 51,57 or greater body perception disturbance in people with longer disease durations. 32 It is important to note that the latter findings do not mean these symptoms progress and worsen over time, as cases that have been resolved are not captured by these studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eine Möglichkeit der Diagnostik besteht daher neben der aktiven Abfrage dieser Wahrnehmungsstörung auch durch den Einsatz verschiedener Fragebögen wie z. B. die auch deutschsprachig validierte "Bath Body Perception Disturbance Scale" [2].…”
Section: Definition Complex Regional Pain Syndrome (Crps)unclassified